A decade later, there are still major issues to be addressed in paediatric anaesthesia. Issue 3 (June 2021) - Habre, Walid; Disma, Nicola
Abstract : Purpose of review: Despite real advances in paediatric anaesthesia management, such as a growing awareness of the relevance of anaesthesia conduct as well as of the lack of evidence for neurotoxicity of anaesthetic agents, it must be said that there are still important questions in our specialty that remain unanswered. Standardization and harmonization of airway management, analgesia techniques and outcome measures are the important issues we are facing at the beginning of this decade. Recent findings: Major improvements in airway management of neonates and infants resulted from the introduction of videolaryngoscopes and the systematic use of nasal oxygenation during endotracheal intubation. Similarly, the increasing popularity of dexmedetomidine has led to the generalization of its use, which, considering that it may produce undesirable effects, poses a challenge for the future. Moreover, recent systematic reviews have confirmed a lack of evidence for the efficacy of many techniques used in clinical practice. Summary: The shift in research from the neurotoxicity of anaesthetic agents to factors related to anaesthetic conduct are discussed. Examples for an improvement in anaesthesia management are highlighted with advocacy for including these evidence-based findings in routine clinical practice. Finally, the impact of using clinically relevant age-related and patient-centred perioperative outcomes is essential for comparing and/or interpreting the safety and efficacy of anaesthesia and analgesia management in children.